Risk management in Nigerian listed commercial banks: The significance of board composition (2013–2023) - Nwafor, Veronica Ogbenyeanu; Nworie, Gilbert Ogechukwu (Goodwood Publishing, 2025)
Purpose: The study examined the effect of board composition on the risk management of listed commercial banks in Nigeria. The specific objective was to determine the effect of board size, board independence, and board gender diversity on the non-performing loan ratio (NPLR). Method: Ex-post facto research design was chosen for the study. The population of the study comprised all the 13 listed commercial banks in Nigeria. A census sampling approach was used to include all the population elements into the sample. Secondary data was collected from the annual audited reports of the banks covering 2013 to 2023. Aside from descriptive analysis, Pearson correlation, Pesaran Cross-sectional Dependence test, and Panel Heteroskedasticity tests were used to assess the validity of the regression model. Panel Estimated Generalized Least Squares was used to test the hypotheses. Results: Board size has a significant positive effect on NPLR (? = 0.003935; p-value = 0.0000); board independence has a significant positive effect on NPLR (? = 0.121012; p-value = 0.0000); board gender diversity has a significant negative effect on NPLR (? = -0.102780; p-value = 0.0000). Conclusions: In conclusion, a well-composed board ensures that banks are resilient to financial shocks while safeguarding the interests of shareholders, customers, and the broader economy. Limitations: The aspects of board composition covered were limited to board size, board independence, and board gender diversity, but did not cover board final literacy and board risk committee. Contribution: Thus, the study recommends that listed commercial banks in Nigeria should have a board size that balances adequate expertise and diversity with the ability to make effective decisions in order to ensure that boards reduce bureaucratic delays in risk management.